The Darwinian shortfall in plants: phylogenetic knowledge is driven by range size. Issue 8 (10th June 2022) - Rudbeck, Alexander V.; Sun, Miao; Tietje, Melanie; Gallagher, Rachael V.; Govaerts, Rafaël; Smith, Stephen A.; Svenning, Jens‐Christian; Eiserhardt, Wolf L.
Abstract : The Darwinian shortfall, i.e. the lack of knowledge of phylogenetic relationships, significantly impedes our understanding of evolutionary drivers of global patterns of biodiversity. Spatial bias in the Darwinian shortfall, where phylogenetic knowledge in some regions is more complete than others, could undermine eco‐ and biogeographic inferences. Yet, spatial biases in phylogenetic knowledge for major groups – such as plants – remain poorly understood. Using data for 337 023 species (99.7%) of seed plants (Spermatophyta), we produced a global map of phylogenetic knowledge based on regional data and tested several potential drivers of the observed spatial variation. Regional phylogenetic knowledge was defined as the proportion of the regional seed plant flora represented in GenBank's nucleotide database with phylogenetically relevant data. We used simultaneous autoregressive models to explain variation in phylogenetic knowledge based on three biodiversity variables (species richness, range size and endemism) and six socioeconomic variables representing funding and accessibility. We compared observed patterns and relationships to established patterns of the Wallacean shortfall (the lack of knowledge of species distributions). We found that the Darwinian shortfall is strongly and significantly related to the macroecological distribution of species' range sizes. Small‐ranged species were significantly less likely to have phylogenetic data, leading to a concentration of the Darwinian shortfall in species‐rich, tropical countries where range sizes are small on average. Socioeconomic factors were less important, with significant but quantitatively small effects of accessibility and funding. In conclusion, reducing the Darwinian shortfall and smoothen its spatial bias will require increased efforts to sequence the world's small‐ranged (endemic) species.